PENGARUH KEBUTUHAN UNIQUENESS, STATUS, DAN HEDONIC VALUE TERHADAP CONSUMER-BRAND IDENTIFICATION DAN BRAND LOYALTY KONSUMEN MEREK-MEREK FASHION MEWAH DI SURABAYA - HERLIUS THEODORE PANGESTU (Jurnal Strategi Pemasaran, 2019)
This study examines the effect of three important values that are closely related to luxury brand, namely uniqueness value, status value, and hedonic value that affect consumer-brand identification toward brand loyalty. This research is conclusive and classified as causal-type research using a quantitative approach. The data was collected through online surveys using a self-administered questionnaire resulting in 101 usable responses. The respondents are consumers who buy and have a luxury brand fashion in Surabaya. The data is used using a Structural Equation Modeling using Partial Least Square technique. Results showed substantial evidence for research hypotheses.